Malpas the Dragon. - Cattanach, Ann (Jessica Kingsley Publishers, 2007)
Malpas the dragon flew all around the world, breathing fire, screaming, moaning and farting. He made everybody afraid. Malpas was treated badly by his parents. They taught him to be a very rude, angry dragon, but this meant that he was also unloved and lonely. Every day he cried stone tears that he sent to his only friend, Haley. But Haley knew the tears were special. She gave them as gifts to lonely children to help warm their hearts. This beautifully illustrated children's book is about loss and survival. It will be enjoyed by children and adults alike, and is ideal for parents and professio.